2011
DOI: 10.1016/j.neuropharm.2010.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The binding sites for benztropines and dopamine in the dopamine transporter overlap

Abstract: Analogues of benztropines (BZTs) are potent inhibitors of the dopamine transporter (DAT) but are less effective than cocaine as behavioral stimulants. As a result, there have been efforts to evaluate these compounds as leads for potential medication for cocaine addiction. Here we use computational modeling together with site-directed mutagenesis to characterize the binding site for BZTs in DAT. Docking into molecular models based on the structure of the bacterial homologue LeuT supported a BZT binding site tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 47 publications
7
84
0
Order By: Relevance
“…The docking results confirmed that the 5-MAPB pose overlaps with the dopamine, amphetamine, 5-APB, MDMA, cocaine and RTI-121 binding sites (Supplemental Figure 2SB). Indeed, comparison of molecular models of dopamine ( Figure 5B), amphetamine ( Figure 5C), 5-APB ( Figure 5D), MDMA ( Figure 5E), 5-MAPB (after an induced-fit protocol, that allows backbone flexibility, Figure 5F), cocaine (Supplemental Figure 2SC) and RTI-121 (Supplemental Figure 2SD) show that these compounds share a binding site at the centre of rDAT and located in a position corresponding to the primary substrate-binding site cavity (S1) seen in previous modelling studies in hDAT (Beuming et al, 2008;Bisgaard et al, 2011). Specifically, in rDAT, aromatic-aromatic stacking interactions are observed between Tyr156 and the catechol ring of dopamine, phenyl ring of amphetamine and the fused benzene and furan rings of 5-APB, 5-MAPB and MDMA.…”
Section: Accepted M Manuscriptsupporting
confidence: 54%
See 1 more Smart Citation
“…The docking results confirmed that the 5-MAPB pose overlaps with the dopamine, amphetamine, 5-APB, MDMA, cocaine and RTI-121 binding sites (Supplemental Figure 2SB). Indeed, comparison of molecular models of dopamine ( Figure 5B), amphetamine ( Figure 5C), 5-APB ( Figure 5D), MDMA ( Figure 5E), 5-MAPB (after an induced-fit protocol, that allows backbone flexibility, Figure 5F), cocaine (Supplemental Figure 2SC) and RTI-121 (Supplemental Figure 2SD) show that these compounds share a binding site at the centre of rDAT and located in a position corresponding to the primary substrate-binding site cavity (S1) seen in previous modelling studies in hDAT (Beuming et al, 2008;Bisgaard et al, 2011). Specifically, in rDAT, aromatic-aromatic stacking interactions are observed between Tyr156 and the catechol ring of dopamine, phenyl ring of amphetamine and the fused benzene and furan rings of 5-APB, 5-MAPB and MDMA.…”
Section: Accepted M Manuscriptsupporting
confidence: 54%
“…We also use a functional test measuring electrically evoked dopamine efflux in the nucleus accumbens, as the brain region involved in reinforcement and addiction, by means of fast cycling voltammetry. We augment our ligand binding and functional data with structural results from computational molecular modelling, docking studies and atomistic molecular dynamics simulations, which have been previously shown to be robust methods for predicting the binding sites of various psychostimulants at human DAT (hDAT) in relation to the substrate binding site (Beuming et al, 2008;Bisgaard et al, 2011). We present here, on the basis of the crystal structure from Drosophila melanogaster dopamine transporter (dDAT) (PDB ID: 4XP1) (Wang et al, 2015), a molecular model of 5-MAPB bound to rat DAT (rDAT), in comparison with that of dopamine, amphetamine, 5-APB, MDMA, cocaine and RTI-121 also bound to rDAT.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…3; Supplemental Table 1), substantiating that SERTCluster 2 and SERT-Cluster 3 do not represent the bioactive binding conformation of fluoxetine in SERT. Interestingly, TM10 residues have previously been suggested to have an important role for inhibitor binding within the S1 site of Drosophila and human DAT (Bisgaard et al, 2011;Penmatsa et al, 2013). Here we show that mutation of residues in TM10 of SERT (Ala486, Val489, Lys490, and Glu493) induce ,3-fold changes in the potency of fluoxetine ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases DAT ligands of diverse structure are overlapping in their protein binding sites. The sites of either benztropine inhibitors or cocaine overlap with the DA site (Beuming et al, 2008;Bisgaard et al, 2011). Allosteric ligands of the DAT have been detected by pharmacological methods (Rothman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%